GAZA IN MEDIA EDITORIAL FRAME (SUARA PEMBARUAN, MEDIA INDONESIA, AND REPUBLIKA) - Sieria, Anita (Institute of Research and Community Outreach - Petra Christian University, 2009)
Gaza strip has became the home for the longest lasting conflict between Israel and Palestine, even when the researcher doing this research, the conflict still remain. This conflict has become an important issue for the international world and has attracted various media coverage from all over the world including Indonesia. Many news, opinions, and editorials are involved in expressing arguments of different interests. Moreover, Indonesia has the largest Moslem population in the world, and therefore the conflict is often brought into the religious realm. Medias with different ideologies produce their reports with different frames. It is no surprise that people may have different perception about a situation in the conflict. This phenomenon, is the reason behind the writers interest in finding out how the Gaza conflict is being framed in Indonesian media editorial. Framing Analysis Method is being used to find out the differences of framing between the following medias: Suara Pembaruan (SP), Media Indonesia (MI), and Republika. It is found that differences in ideology influenced the framing of media editorial. Suara Pembaruan builds a frame that shows that Palestine (Hamas) is an extreme cluster causing negative effects, while Israel and United Nations?s resolution viewed from a positive point of view. MI sees this conflict as political conflict. Republika perceives this conflict as an impact of Israel violence as well the paralyzed condition of the United Nation.